Risk Factors for Central Lymph Node Metastases and Benefit of Prophylactic Central Lymph Node Dissection in Middle Eastern Patients With cN0 Papillary Thyroid Carcinoma - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Ahmed, Saeeda O.; DeVera, Felisa; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Oncology, 2022)
Background Prophylactic central lymph node dissection (PCLND) for adult patients with papillary thyroid carcinoma (PTC) is still a matter of debate. Data on incidence, risk and benefits of PCLND in Middle Eastern patients is lacking. Therefore, we aimed to identify the incidence and predictive clinico-pathological and molecular marker of PCLND in adult patients with clinically node negative (cN0) Middle Eastern PTC. Methods This retrospective study included 942 adult Middle Eastern patients with cN0 PTC who underwent total thyroidectomy (TT) or TT+PCLND. Clinico-pathological associations of central lymph node metastasis (CLNM) were assessed. Multivariate analysis was performed using logistic regression and Cox proportional hazards model. Results 213 patients underwent PCLND and 38.0% (81/213) had positive CLNM. Multivariate analysis demonstrated age ≤55 years (Odds Ratio (OR) = 7.38; 95% Confidence Interval (CI) = 1.59 – 34.31; p = 0.0108), tumor bilaterality (OR = 3.01; 95% CI = 1.01 – 9.21; p = 0.0483), lymphovascular invasion (OR = 2.92; 95% CI = 1.18 – 7.23; p = 0.0206) and BRAF mutation (OR = 3.24; 95% CI = 1.41 – 7.49; p = 0.0058) were independent predictors of CLNM in adult PTC. Furthermore, patients who underwent PCLND showed significant association with improved recurrence-free survival (RFS; p = 0.0379). Multivariate analysis demonstrated that PCLND was an independent predictor of improved recurrence-free survival. Conclusions cN0 Middle Eastern PTC patients treated with PCLND showed a significantly better prognosis. PCLND was effective in improving RFS in Middle Eastern PTC patients and should be encouraged for patients with potential risk factors for CLNM.